Mechanical, physical and thermal properties of rattan fibre-based binderless board - Ahmad, Zuraida; Tajuddin, Maisarah; Wan Mohd Yusof, Wan-Shazlin Maisarah (Forest Research Institute Malaysia, 2017)
About 50% is of harvest is wasted when producing rattan furniture. With such huge amount of waste, we undertook a study to convert rattan waste into binderless board with superior properties. This study compared the mechanical and physical properties and morphologies of binderless boards manufactured from rattan fibres with boards made from kenaf, coconut husk and sugarcane bagasse using hot press process. Raw fibres were characterised using scanning electron microscopy and thermal analysis to study their suitability in producing self-bonded board, and then dried in the oven before being hot pressed at a pressure of 147.5 kPa. Modulus of rupture (MOR), internal bonding strength, thickness swelling and water absorption of the manufactured binderless boards were evaluated based on the Japanese Industrial Standards. Results showed that rattan binderless boards exhibited slightly lower MOR and higher internal bonding strength with good dimensional stability compared with the rest of the binderless boards. It was concluded that rattan fibres have high potential to be used as binderless boards under hot press conditions.